Role of type 2A phosphatase regulatory subunit B56α in regulating cardiac responses to β-adrenergic stimulation in vivo. Issue 3 (10th September 2018) - Puhl, Sarah-Lena; Weeks, Kate L; Güran, Alican; Ranieri, Antonella; Boknik, Peter; Kirchhefer, Uwe; Müller, Frank U; Avkiran, Metin
Abstract: Aims: B56α is a protein phosphatase 2A (PP2A) regulatory subunit that is highly expressed in the heart. We previously reported that cardiomyocyte B56α localizes to myofilaments under resting conditions and translocates to the cytosol in response to acute β-adrenergic receptor (β-AR) stimulation. Given the importance of reversible protein phosphorylation in modulating cardiac function during sympathetic stimulation, we hypothesized that loss of B56α in mice with targeted disruption of the gene encoding B56α ( Ppp2r5a ) would impact on cardiac responses to β-AR stimulation in vivo . Methods and results: Cardiac phenotype of mice heterozygous (HET) or homozygous (HOM) for the disrupted Ppp2r5a allele and wild type (WT) littermates was characterized under basal conditions and following acute β-AR stimulation with dobutamine (DOB; 0.75 mg/kg i.p.) or sustained β-AR stimulation by 2-week infusion of isoproterenol (ISO; 30 mg/kg/day s.c.). Left ventricular (LV) wall thicknesses, chamber dimensions and function were assessed by echocardiography, and heart tissue collected for gravimetric, histological, and biochemical analyses. Western blot analysis revealed partial and complete loss of B56α protein in hearts from HET and HOM mice, respectively, and no changes in the expression of other PP2A regulatory, catalytic or scaffolding subunits. PP2A catalytic activity was reduced in hearts of both HET and HOM mice. There were no differences in the basal cardiac phenotype between genotypes. Acute DOB stimulation induced the expected inotropic response in WT and HET mice, which was attenuated in HOM mice. In contrast, DOB-induced increases in heart rate were unaffected by B56α deficiency. In WT mice, ISO infusion increased LV wall thicknesses, cardiomyocyte area and ventricular mass, without LV dilation, systolic dysfunction, collagen deposition or foetal gene expression. The hypertrophic response to ISO was blunted in mice deficient for B56α. Conclusion: These findings identify B56α as a potential regulator of cardiac structure and function during β-AR stimulation.